MODEL PERCEIVED RISK AND TRUST: E-WOM AND PURCHASE INTENTION (THE ROLE OF TRUST MEDIATING IN ONLINE SHOPPING IN SHOPEE INDONESIA) - Rafqi Ilhamalimy, Ridho; Ali, Hapzi (Dinasti Publisher, 2021)
Purpose. This study discusses the Role of Trust in Mediating eWOM and Perceived Risk of Online Purchase Intention in Shopee. Design / methodology / approach. This study was conducted in Jakarta using 185 samples using SEM-PLS data analysis method. Findings. Trust is able to act as mediating between ewom and also perceived risk of online purchase intention in shopee. Practical implication. Shopee companies should be able to provide reliability in services and various features, and also increase security when consumers shop online at Shopee, because it can create an interest in buying online on an ongoing basisTheoretical implications. This research has limitations that can be used as advice or input for further research.